ARTICULATORY AND ACOUSTIC FEATURES OF UNSTRESSED VOCALISM IN THE ENGLISH LANGUAGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article “Articulatory and Acoustic Features of Unstressed Vocalism in the English Language” provides a comprehensive analysis of vowel reduction and the functioning of unstressed vowels in English phonetics. The study emphasizes the central role of the neutral vowel /ə/ (schwa) as the core element of unstressed vocalism, describing its positional variants and articulatory features as outlined by D. Jones and later phoneticians. It also highlights the occurrence of other unstressed vowels such as /ɪ/ and /u/, explaining their distributional patterns and dependence on stress and position within the word. Drawing on works by D.Jones, G. P. Torsuev, G. Kelly, P. Roach, G. Knowles, and others, the article categorizes vowels in unstressed syllables into three types ‒ full, semi-weak, and reduced ‒ and clarifies their usage in different speech styles (careful, rapid, and literary). Particular attention is paid to semi-weak vowels that represent an intermediate stage between full and fully reduced forms. The study concludes that while /ə/ dominates in unstressed positions, its articulation varies according to word structure and syllabic position, resulting in a continuum of vowel weakening. Overall, the article presents a detailed theoretical overview of English unstressed vocalism, synthesizing classical and modern phonetic research to illustrate the dynamic nature of vowel reduction in English pronunciation.